Gratitude in AI-based Quranic Exegesis: Between Meta AI and ChatGPT - Nasir, Muhammad Najri; Nurrohim, Ahmad (Universitas Muhammadiyah Surakarta, 2024)
Gratitude is one of the fundamental concepts in human life, reflecting a sense of thankfulness for the blessings given. In the era of digital technology, artificial intelligence (AI) presents a new perspective in understanding and expressing the concept of gratitude through interactions with users. This article aims to comparatively examine the approaches of two AI platforms, Meta AI and ChatGPT, in understanding and conveying the meaning of gratitude based on user input. This study employs a descriptive qualitative method, With a comparative approach to analyze how Meta AI and ChatGPT understand and convey the concept of gratitude. This study is qualitative in nature and aims to reveal the differences and similarities in the responses of the two artificial intelligence platforms regarding the theme of gratitude. The results of the study indicate that gratitude is an attitude of the heart, speech, and actions in acknowledging and utilizing Allah's blessings. Gratitude is not merely expressed in words but must also be manifested in tangible actions that align with Shariah. Gratitude also has reciprocal consequences: if one is grateful, Allah will increase the blessings; if one is ungrateful, they will face a painful punishment. The additional blessings promised by Allah encompass both worldly and spiritual aspects, not only in material form but also in blessings, happiness, and closeness to Allah. Ungratefulness does not only mean denying the blessings, but also misusing or failing to use them in accordance with Allah's will.